1998
DOI: 10.2136/sssaj1998.03615995006200030039x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Methane, Nitrous Oxide, and Carbon Dioxide Emissions from Drained Grasslands

Abstract: Emissions of CH4, N2O, and CO2 from soils are the result of a number of biological and physical processes, each influenced by several environmental and management factors exhibiting spatial variability. This study aimed to assess the spatial variability and spatial dependence of CH4, N2O, and CO2 emissions and their underlying soil processes and properties from grasslands on drained peat soil (Terric Histosol). Emissions and possible controlling factors were measured at a field location in Sweden. Measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 0 publications
4
24
0
1
Order By: Relevance
“…Several authors have reported on the CH 4 emissions from drained organic soils (Glenn et al , 1993; e.g. Nykänen et al , 1995; Van den Pol‐van Dasselaar et al , 1998). All found that drained organic soils used for farming were a negligible source or sink of CH 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reported on the CH 4 emissions from drained organic soils (Glenn et al , 1993; e.g. Nykänen et al , 1995; Van den Pol‐van Dasselaar et al , 1998). All found that drained organic soils used for farming were a negligible source or sink of CH 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Kelly & Canham 1992; Halvorson et al . 1994; Palmer & White 1994; van den Pol‐van Dasselaar et al . 1998).…”
Section: Discussionunclassified
“…High temporal variability of emissions from a fertilized banana plantation in Costa Rica resulted in an underestimation of mean annual N20 emissions if monthly sampled flux data are extrapolated compared to extrapolation of fluxes sampled on a fertilization event basis [Veldkamp and Keller, 1997]. Temporal variability and short-time responses of fluxes on changes in controlling factors has been demonstrated using automated sampling and analysis systems [Brumme and Beese, 1992;Crill et al, 1999].…”
Section: Introductionmentioning
confidence: 99%